MOF nanoparticles as heterogeneous catalysts for direct amide bond formations - Abánades Lázaro, Isabel; Forgan, Ross S; Cirujano, Francisco G (Dalton transactions : an international journal of inorganic chemistry, 2022)
The influence of composition and textural characteristics of a family of ultra-small isoreticular UiO-type metal-organic frameworks (MOFs) with different functionalized and extended linkers on their catalytic performance is evaluated. Two direct amide bond formations across four different substrates (benzylamine + phenylacetic acid and aniline + formic acid) are employed as proof-of-concept reactions to test the activity of the Zr-MOF nanoparticles. The reaction rates of amide bond formation are evaluated against physico-chemical properties such as crystallinity, porosity, particle size or linker functionality, alongside the Lewis acid and hydrophobic properties of the MOFs, in order to gain insights into the catalytic mechanism and optimal properties for its enhancement.